2008
DOI: 10.1080/10406630701779434
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polycyclic Aromatic Hydrocarbons in Amniotic Fluid Samples From Smokers and Nonsmokers

Abstract: Previous studies from this laboratory have focused on the characterization of blood protein adducts formed in utero as a result of maternal smoking during pregnancy. These biological samples, obtained during the third trimester of pregnancy, at delivery, have clearly shown a correlation between maternal smoking histories and exposure of the fetus to tobacco smoke carcinogens, including 4-aminobiphenyl and benzo(a)pyrene. In the present study, we examined exposure of the fetus during the first trimester of preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 165 publications
(167 reference statements)
2
2
0
Order By: Relevance
“…The measured concentrations of Σ 12 OH-PAHs in urine from China and India were similar to those reported for the U.S. population in 2001–2002 (geometric mean: 5610) . The concentrations of Σ 12 OH-PAHs determined in urine in our study were 1–2 orders of magnitude lower than those reported for occupationally exposed populations, such as coke oven workers in Poland (median: 155 000 pg/mL), and smokers in Germany (mean: 15 000 pg/mL) …”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The measured concentrations of Σ 12 OH-PAHs in urine from China and India were similar to those reported for the U.S. population in 2001–2002 (geometric mean: 5610) . The concentrations of Σ 12 OH-PAHs determined in urine in our study were 1–2 orders of magnitude lower than those reported for occupationally exposed populations, such as coke oven workers in Poland (median: 155 000 pg/mL), and smokers in Germany (mean: 15 000 pg/mL) …”
Section: Resultssupporting
confidence: 81%
“…The geographic pattern of PAH concentrations in the atmosphere of several Asian countries is consistent with the concentrations of OH-PAHs measured in urine from these countries. The concentrations of Σ 12 OH-PAHs in urine from Malaysia and Japan were comparable to those reported for Germany (mean: 3220 pg/mL) . The measured concentrations of Σ 12 OH-PAHs in urine from China and India were similar to those reported for the U.S. population in 2001–2002 (geometric mean: 5610) .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…4 PAHs and PAH-DNA adducts have been found in placental tissues of women, amniotic fluid samples and umbilical cord blood samples from newborns. [5][6][7][8][9][10] PAH adducts can disrupt the cell's microenvironment, 1 11 to which the rapidly growing and differentiating cells of the fetus may be particularly vulnerable. 12 PAHs may also lead to periods of fetal hypoxia through reduced placental blood flow.…”
Section: Introductionmentioning
confidence: 99%